2014
DOI: 10.1002/cbf.3052
|View full text |Cite
|
Sign up to set email alerts
|

miR181c promotes apoptosis and suppresses proliferation of metanephric mesenchyme cells by targeting Six2 in vitro

Abstract: Increasingly recognized importance has been assumed for microRNA (miRNA) in the regulation of the delicate balance of gene expression. In our study, we aimed to explore the regulation role of miR181c towards Six2 in metanephric mesenchyme (MM) cells. Bioinformatics analysis, luciferase assay and semi-quantitative real-time (RT) PCR, subsequently RT PCR, Western blotting, 5-ethynyl-2'-deoxyuridine cell proliferation assay, Cell Counting Kit-8 assay, immunofluorescence and flow cytometry, were employed to verify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…Li and colleagues, in an acute lung injury model, have shown that overexpressed miR-181a is related to decreased Bcl2 protein level; conversely, the inhibition of miR-181a increase Bcl2 levels (Li et al, 2016). The current study confirming Lv et al (2014) demonstrated that miR-181c regulates negatively, the expression of Six2 expression and cell proliferation, in parallel to the loss of mesenchymal cells phenotype during kidney development in LP 17-DG offspring.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…Li and colleagues, in an acute lung injury model, have shown that overexpressed miR-181a is related to decreased Bcl2 protein level; conversely, the inhibition of miR-181a increase Bcl2 levels (Li et al, 2016). The current study confirming Lv et al (2014) demonstrated that miR-181c regulates negatively, the expression of Six2 expression and cell proliferation, in parallel to the loss of mesenchymal cells phenotype during kidney development in LP 17-DG offspring.…”
supporting
confidence: 75%
“…In the kidney ontogenic context, several researchers have demonstrated that miRNAs are indispensable for nephron development (Chu et al, 2014;Harvey et al, 2008;Lv et al, 2014;. Prior studies have shown that during kidney development, the underexpression of miRNAs in MM progenitor cells results in a premature reduction of cell proliferation and, consequently, decreased the number of nephrons (Ho et al, 2011;Nagalakshmi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These research studies implied that the research of the upstream regulatory factor towards Six2 is of great importance. According to the limited associated reports, the miR181 family is able directly target the 3′UTR of Six2 and suppress its expression [18,19], Recombination signal binding protein for immunoglobulin kappa J region (Rbpj) is sufficient for the down-regulation of Six2 [20], Notch2 can shut down the Six2 mediated program for progenitor maintenance [21], and Pax2/Eya1/Hox11 complex binds to the proximal promoter of Six2 and thus regulates its expression [22]. …”
Section: Discussionmentioning
confidence: 99%
“…In the kidney ontogenic context, several researchers have demonstrated that miRNAs are indispensable for nephron development (Chu et al, 2014;Harvey et al, 2008;Lv et al, 2014;. Prior studies have shown that during kidney development, the underexpression of miRNAs in MM progenitor cells results in a premature reduction of cell proliferation and, consequently, decreased the number of nephrons (Ho et al, 2011;Nagalakshmi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%